On the Theory of Price Agreements 1 - Brems, Hans (Quarterly Journal of Economics, 1951)
I. Introduction, 252. — II. Assumptions, 253. — III. The duopolists' hypotheses about rival behavior, 255. — IV. The duopolists' maximum effective, expected profits, 257. — V. Minimum requirements of A and B confronted, 258. — VI. Chances for agreement, 258. — VII. The result of bargaining, 260. — VIII. Lesson on bargaining techniques, 260.